2023
DOI: 10.1017/jfm.2023.5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a surface tension driven colloidal motor based on an active Janus particle encapsulated in a liquid drop

Abstract: A colloidal motor driven by surface tension forces is theoretically designed by encapsulating an active Janus particle in a liquid drop which is immiscible in the suspending medium. The Janus particle produces an asymmetric flux of a solute species which induces surface tension gradients along the liquid–liquid interface between the drop and the surrounding fluid. The resulting Marangoni forces at the interface propel the compound drop/Janus particle system. The propulsion speeds of the motor are evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…Later Shaik et al 46 studied the locomotion of an eccentric active compound particle in the presence of surfactants and identified the steady eccentric configurations. Recently, Chembai Ganesh et al 47 analytically studied the locomotion of an active Janus particle in a surfactant-laden droplet and demonstrated that the Marangoni stresses assist the encapsulated Janus particle in driving the cargo (confining droplet). All these studies assume that the confining droplet is spherical (non-deforming) and analyze the translational dynamics of active compound particles.…”
Section: Introductionmentioning
confidence: 99%
“…Later Shaik et al 46 studied the locomotion of an eccentric active compound particle in the presence of surfactants and identified the steady eccentric configurations. Recently, Chembai Ganesh et al 47 analytically studied the locomotion of an active Janus particle in a surfactant-laden droplet and demonstrated that the Marangoni stresses assist the encapsulated Janus particle in driving the cargo (confining droplet). All these studies assume that the confining droplet is spherical (non-deforming) and analyze the translational dynamics of active compound particles.…”
Section: Introductionmentioning
confidence: 99%